Surface Texturing of Vitamin E Blended UHMWPE for Reduction of Wear - Sagbas, B.; Durakbasa, M. N. (POLISH ACAD SCIENCES INST PHYSICS, 2014)
Ultra high molecular weight polyethylene (UHMWPE) has been the most commonly used bearing material in artificial hip and knee replacements. But wear and wear debris of UHMWPE has been the most important problem which cause aseptic loosening and revision surgery of these replacements. For enhangement of wear resistance, new generation UHMWPE materials have been developed and different surface modification techniques have been tried. The objective of this study is to determine the effect of surface dimples on wear behavior of conventional UHMWPE and vitamin E blended UHMWPE (VE-UHMWPE) in ultra-pure water lubrication conditions. Pin-on-disc tribotester was used for measurement of friction coefficient and wear. 0.5 mm in diameter dimples were machined on the surfaces of UHMWPE and VE-UHMWPE discs. CoCrMo pins were used as counter surface. Results were evaluated in terms of materials and presence of dimples.
Keywords: ALPHA-TOCOPHEROL; RESISTANCE; Physics